An Actor‐Partner Model of Relationship Effort and Marital Quality. Issue 5 (December 2014) - Shafer, Kevin; Jensen, Todd M.; Larson, Jeffry H.
<x xml:space="preserve">Abstract</x> Several studies demonstrate a strong, positive association between relationship effort, which may be defined as one's attitude and behavior toward improving a romantic relationship, and relationship quality. Relationship self‐regulation scholars have argued that effort is dyadic, where one partner's effort influences the other partner's perceptions of relationship quality and vice versa. Yet studies addressing actor‐partner effects for relationship effort are lacking. The authors address this issue by using actor‐partner interdependence models and data from 795 first married couples in the Relationship Evaluation Survey. The authors find that (a) perceptions of one's own effort and their spouse's effort are positively associated with satisfaction and divorce proneness in actors, (b) husband report of his own satisfaction is positively affected by wife's effort, and (c) husband's effort is positively associated with wife's satisfaction. Results demonstrate the importance of actor and partner effects in building satisfying and stable relationships.